An elementary theory of global supply chains - Arnaud Costinot; Jonathan E. Vogel; Su Wang (Center for Economic Studies and ifo Institute (CESifo), 2011)
This paper develops an elementary theory of global supply chains. We consider a world economy with an arbitrary number of countries, one factor of production, a continuum of intermediate goods, and one final good. Production of the final good is sequential and subject to mistakes. In the unique free trade equilibrium, countries with lower probabilities of making mistakes at all stages specialize in later stages of production. Because of the sequential nature of production, absolute productivity differences are a source of comparative advantage among nations. Using this simple theoretical framework, we offer a first look at how vertical specialization shapes the interdependence of nations.
Keywords: F10; 330; Lieferanten-Kunden-Beziehung; Globalisierung; Komparativer Kostenvorteil; Vertikale Konzentration; Internationale Arbeitsteilung; Außenwirtschaftstheorie; Theorie